Saving behavior and the asset price 'bubble' in Japan : analytical studies - Baumgartner, Ulrich ed. (IMF WashingtonUS, 1995)
Considers whether Japan's saving can be characterized as excessively high and analyses developments in Japan's capital flows since 1980. Examines the potential impact of an aging population on Japan's saving rate and provides a long-run simulation analysis of the effects of population aging. Describes the evolution of asset prices during and after the bubble period, assess the role played by various factors in driving asset prices during this episode, and provides estimates on real activity. Examines the relationship between macroeconomic variables and asset price inflation in the 1980s.